Anabolic Androgenic Steroid (AAS) Related Deaths: Autoptic, Histopathological and Toxicological Findings - Frati, Paola; P. Busardo, Francesco; Cipolloni, Luigi; De Dominicis, Enrico; Fineschi, Vittorio (Current Neuropharmacology, 2015)
Anabolic androgenic steroids (AASs) represent a large group of synthetic derivatives of testosterone, produced to maximize anabolic effects and minimize the androgenic ones. AAS can be administered orally, parenterally by intramuscular injection and transdermally. Androgens act by binding to the nuclear androgen receptor (AR) in the cytoplasm and then translocate into the nucleus. This binding results in sequential conformational changes of the receptor affecting the interaction between receptor and protein, and receptor and DNA. Skeletal muscle can be considered as the main target tissue for the anabolic effects of AAS, which are mediated by ARs which after exposure to AASs are up-regulated and their number increases with body building. Therefore, AASs determine an increase in muscle size as a consequence of a dose-dependent hypertrophy resulting in an increase of the cross-sectional areas of both type I and type II muscle fibers and myonuclear domains. Moreover, it has been reported that AASs can increase tolerance to exercise by making the muscles more capable to overload therefore shielding them from muscle fiber damage and improving the level of protein synthesis during recovery. Despite some therapeutic use of AASs, there is also wide abuse among athletes especially bodybuilders in order to improve their performances and to increase muscle growth and lean body mass, taking into account the significant anabolic effects of these drugs. The prolonged misuse and abuse of AASs can determine several adverse effects, some of which may be even fatal especially on the cardiovascular system because they may increase the risk of sudden cardiac death (SCD), myocardial infarction, altered serum lipoproteins, and cardiac hypertrophy. The aim of this review is to focus on deaths related to AAS abuse, trying to evaluate the autoptic, histopathological and toxicological findings in order to investigate the pathophysiological mechanism that underlines this type of death, which is still obscure in several aspects. The review of the literature allowed us to identify 19 fatal cases between 1990 and 2012, in which the autopsy excluded in all cases, extracardiac causes of death.
Keywords: toxicity